Pemaknaan Fatherhood dalam Konten Tiktok @Abe_daily Bagi Mahasiswa di Kabupaten Garut - Rifqi Rahman Zaidan; Ismira Febrina; Mohammad Firmansyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine how audiences interpret the concept of fatherhood through the TikTok content of @Abe_daily, which portrays an affectionate and actively involved father figure. Fatherhood is not only about financial responsibility but also involves emotional engagement, caregiving, and an active presence in a child’s life. In Indonesia, however, traditional parenting norms still prevail, where fathers are primarily viewed as breadwinners, contributing to the phenomenon of fatherlessness. The rise of new media, particularly TikTok, has created a platform for reshaping public perceptions of fatherhood. Using Stuart Hall’s encoding-decoding theory, this study analyzes how fatherhood is constructed in digital media and how audiences interpret such representations. The research employs a qualitative reception analysis method, collecting data through in-depth interviews with selected informants. The findings reveal three categories of audience interpretation: dominant (agreeing with the portrayal of modern fatherhood), negotiated (recognizing positive values while considering cultural factors), and oppositional (rejecting the idea due to traditional views). The study highlights the role of social media in shaping new ideals of fatherhood, challenging patriarchal norms, and offering positive role models. These findings suggest that the concept of fatherhood is evolving, influenced by media portrayals and societal perceptions. This research contributes to discussions on the role of digital media in reconstructing family structures and parenting practices in Indonesia.